Community perceptions of a mine recruitment centre in Pafuri and the development of a cultural heritage site in the Greater Limpopo Transfrontier Park - Hansen, Heidi Suzanne (My University, 2009)
The TEBA recruitment centre in Pafuri has come under discussion and debate with the developments of the GLTP. The site has played a signficant role in the social and economic history of this dynamic permeable borderzone. Through documenting the experienced memory and meaning of the site on either side of the border, developments of the site as a heritage site in a Transboundary protected area have been considered. Ethnographic interviews were used to document these meanings. TEBA is a reminder of a prosperous past amidst the current desperate poverty and unemployment and with little faith in the government, the Kruger and Limpopo Parks, TEBA is looked to for the provision of employment. This lack of faith in the parks and their insensitivity towards the historical significance reflects the lack of real transformation in conservation philosophy that the Transfrontier Initiative claims to have achieved. In order for the site to be holistically and ethically represented, greater and more real incorporation of stakeholders is necessary.
Keywords: Mine recruitment; cultural heritage mananagment in protected areas; Pafuri; community perceptions